(untitled) (Tanzania Journal for Population studies and Development, 2020)
This paper uses micro data from Tanzanian manufacturing firms to examine the influence of education policy on returns to schooling. The question stems from the fact that over time education systems and policies are likely to change, hence workers who attended the same level of schooling in different years are likely to display differences in returns to schooling. The paper contributes knowledge in the empirical estimation of returns to schooling where instrumental variables are usually individual characteristics such as parental background or education background. In this paper, education policy differences that affect school attendants differently are used as instruments instead. There are views that education policy is non-exogenous, and hence cannot be instrumental in endogenous schools. In this paper an attempt is made to see the extent to which this view can hold in our empirical estimations. This paper has the advantage of making use of panel data to directly estimate the effect of education policy on earnings, while controlling for schooling. The resulting estimates of the study strongly support that returns to education have changed over time. The results based on years of schooling also support this finding, but when we control for firm fixed effects, they lose their statistical significance.